Crystal structure, Hirshfeld surface and frontier molecular orbital analysis of 9-(3-bromo-4-hydroxy-5-methoxyphenyl)-3,3,6,6-tetramethyl-3,4,5,6,7,9-hexahydro-1H-xanthene-1,8(2H)-dione - N. Suresh Babu (International Union of Crystallography, 2021)
In the fused ring system of the title compound, C24H27BrO5, the mean plane and maximum deviations of the central pyran ring are 0.0384 (2) and 0.0733 (2) Å, respectively. The cyclohexenone rings both adopt envelope conformations with the tetra-substituted C atoms as flap atoms, whereas the central pyran ring adopts a flattened boat conformation. The central pyran and phenyl substituent rings are almost perpendicular to each other, making a dihedral angle of 89.71 (2)°. In the crystal, pairs of molecules are linked via O—H...O hydrogen bonds, forming inversion dimers with an R22(20) ring motif. A Hirshfeld surface analysis indicates that the most important contributions to the crystal packing are from H...H (50.6%), O...H/H...O (22.9%) and C...H/H...C (11.1%) contacts. Quantum chemical calculations for the frontier molecular orbitals were undertaken to determine the chemical reactivity of the title compound.